Narativ i moralni diskurs o braku u Knjizi o Tobiji - Beck, Boris (2018)
Knjiga o Tobiji napisana je oko 3. st. pr. Kr. Kanonskom je smatraju katolici i pravoslavni, a protestanti i Židovi ne. Pripovijest nije historijska, nego fiktivna, vrlo dinamične fabule, pri čemu sadrži brojne pouke u starozavjetnom duhu, napose deuteronomističke teologije. Brak joj je središnja tema, a ideal braka predstavlja tjelesna čistoća, borba protiv požude, vjernost, monogamnost i trajnost ženidbenog saveza. Na više mjesta prikazuje se kako su ljubav, privrženost i obzirnost nužni za uspješan brak. Važan je uvjet i endogamnost ženidbe, kako bi supružnici lakše sačuvali i prakticirali vjeru. Na koncu se molitva – kao izraz povjerenja u Boga – postavlja kao temelj braka čija svrha nadilazi erotsku i prokreativnu funkciju, a ističe se važnost posvećivanja. Knjiga o Tobiji tako u zabavnom obliku čitatelju nudi moralnu pouku koja se nadovezuje na biblijski moral.
Tobit was written around the third century B.C. It is considered canonical by the Catholics and the Orthodox believers, but not by Protestants and the Jews. The story is not historical but fictional, with a very dynamic narrative, containing numerous lessons in the spirit of the OT, particularly those relating to Deuteronomy theology. The central theme of the book is marriage and the ideal marriage is portrayed in terms of physical purity, struggling against lust, faithfulness, monogamy, and the permanence of the marriage covenant. It is pointed out in many places that love, fondness, and consideration are necessary for a successful marriage. Another important condition is the endogamy of marriage, so that the spouses would be able to keep and practice their faith more easily. And finally, prayer as the expression of trust in God is posited as the foundation of a marriage which purpose transcends the erotic and procreative functions and emphasis is also placed on the importance of consecration. So in a fun way, Tobit offers a moral lesson which ties in with Biblical morality.
Bibliografske bilješke uz tekst ; bibliografija: 19 jed.
Sažetak ; Abstract.
Keywords: Knjiga o Tobiji; Brak -- Bog -- Ljubav -- Moral -- Privrženost